Diseño y elaboración de un proceso para aprovechar las lecciones aprendidas en la gerencia de tecnología de Colsubsidio, tomando como caso de estudio tres proyectos (2015)
The present degree work is developed taking into account the stages that make up the research. Taking into account the needs of graduate work qualitative research was developed, which is associated with the description of the process of lessons learned that seeks to characterize facts and processes with questions of who, where, when and how, from interviews conducted to project team officials. The purpose of the degree work is to contribute to the growth of the Technology Management from the construction of new knowledge, transforming the experiences of the project team into an intellectual asset for the organization. Finally, the conclusions and recommendations coming from the research and the proposal to shape the future work coming from the present investigation are recorded.